Teaching ont three-dimensional presentation does not improve the understanding of according CT images: a randomized controlled study - Metzler, Rebecca; Bruckner, Thomas; Büchler, Markus W.; Kadmon, Martina; Müller, Beat P.; Fischer, Lars (Teaching and learning in medicine, 2012)
Background: Randomized studies have already described the advantages of three dimensional (3D) presentations in understanding complex spatial interactions. However, the clinical setting is mainly characterized by presentations of two dimensional (2D) images. Purpose: This study evaluates whether training on 3D presentation enhances the understanding of 2D images. Methods: A teaching module was used consisting of one learning part and two examination parts (EP). Students were randomized to training with either 2D or 3D. Results: This study of 73 students showed that training on 3D presentations did not improve the ability to interpret 2D images. Further, the results revealed no significant differences between the results of Week 1 (2D: M = 6.5, SD = 1.8; 3D: M = 6.6, SD = 1.4; p > .95) and Week 2 (2D: M = 6.1, SD = 1.9; 3D: M = 6.0, SD = 1.4; p > .7). There were no significant gender differences. However, students randomized to 2D who completed only the first EP performed significantly worse if compared to students who completed both EP ( p = .04). Conclusions: This randomized controlled study shows that correct interpretation of 2D imaging does not differ in students trained with either 3D or 2D.